2019
DOI: 10.21873/invivo.11697
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocyte Activation Is Correlated With the Presence of Anti-EBV in Patients With Laryngeal Squamous Cell Carcinoma

Abstract: Background/Aim: Chronic viral infection is an important risk factor in the development of cancer. Failure of immune response to clear the oncogenic infection can facilitate cancer progression. The aim of the present study was to analyze early and late activation of T-lymphocytes related to Epstein-Barr virus (EBV) infection by the expression of markers of activation (CD69, CD25) on the surface of Tlymphocytes (CD3 + , CD4 + , CD8 +) in patients bearing laryngeal cancer according to absence/presence immunoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Therefore, dysfunction of the immune response in removing the oncogenic EBV infection may increase the risk of cancer progression. Although we did not find a significant association between CD3 expression and EBV infection in the larynx, patients with LSCC and EBV infection may have a lower proportion of late activated T lymphocytes in the peripheral blood compared to patients without EBV infection [70]. Therefore, investigating peripheral blood T lym-phocytes may help us to comprehensively understand the possible mechanisms of LR and relapse in EBV-related LSCC.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, dysfunction of the immune response in removing the oncogenic EBV infection may increase the risk of cancer progression. Although we did not find a significant association between CD3 expression and EBV infection in the larynx, patients with LSCC and EBV infection may have a lower proportion of late activated T lymphocytes in the peripheral blood compared to patients without EBV infection [70]. Therefore, investigating peripheral blood T lym-phocytes may help us to comprehensively understand the possible mechanisms of LR and relapse in EBV-related LSCC.…”
Section: Discussionmentioning
confidence: 55%
“…The 31 systematically reviewed studies were carried out in 19 different countries in Europe (n = 12) [6,[10][11][12][13][14][15][16][17][18][19][20], Asia (n = 8) [21][22][23][24][25][26][27][28], North America (n = 5) [3,[29][30][31][32], Eurasia (n = 3) [4,5,33], Oceania (n = 1) [34], South America (n = 1) [2], and concomitantly in North America and Europe (n = 1) [35] (Table 1).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In this scenario, Epstein-Barr virus (EBV) arises as a potential candidate considering all the evidence gathered so far on its oncogenic role in several lymphoid and epithelial malignancies, including head and neck squamous cell carcinomas (HNSCC) [5]. EBV is etiologically linked to undifferentiated nasopharyngeal carcinoma (NPC) [6], and a recent meta-analysis has shown that EBVinfected individuals have a 2.5 times higher risk for developing oral carcinoma [7].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA have an important regulatory function in disease by interacting with disease-related miRNA [5]. According to a paper published in 2015, circRNA can already be used as a reliable biological signal for cancer diagnosis [6]. Moreover, in recent years, there have been literatures showing that the expression of some circRNA in LSCC patients is signi cantly different from that in normal adjacent tissues, and it is believed that there are potential new biomarkers in these signi cantly different circRNA [7].…”
Section: Introductionmentioning
confidence: 99%